Structural basis for rice starch multi‐digestible fractions revealed by consecutive reaction kinetics model - Li, Cheng (Journal of the science of food and agriculture, 2023)
BACKGROUND Starch‐based foods (e.g. rice) usually contain multiple starch fractions with distinct digestion rate constants, although their nature is currently unknown. The present study applied the recently developed consecutive reaction kinetics model to fit the in vitro digestion curves for starch fractions deconvoluted from the overall digestograms to differentiate their binding and catalysis rates to starch digestive enzymes. The fitting parameters were then correlated with starch molecular structures obtained from published data to understand starch structural features determining the binding and catalytic rate constants. RESULTS Binding and catalysis rates for the rapidly (RDF) and slowly digestible starch fraction (SDF) were controlled by distinct starch structural features. Typically, (i) the binding rate constant for RDF was negatively correlated with the amount of amylose short to intermediate chains, whereas it was positively correlated with the relative length of amylopectin intermediate chains; (ii) the catalysis rate constant for RDF was negatively correlated with the amount of amylose short to intermediate chains, relative length of amylose intermediate chains and amount of amylopectin long chains, whereas it was positively correlated with starch molecular size as well as relative length of amylopectin intermediate chains; (iii) and the catalysis rate constant for SDF was negatively correlated with the amount of amylopectin long chains, whereas it was positively correlated with starch molecular size. CONCLUSION These results provide a better understanding of the nature of different starch digestible fractions and the development of foods such as rice with slow starch digestibility. © 2023 Society of Chemical Industry.